2014
DOI: 10.1155/2014/304361
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants of Malaria among Under-Five Children in Ghana

Abstract: Background. Malaria is an entrenched global health challenge particularly in the sub-Saharan African countries. However, in Ghana, little is known about the determinants of malaria prevalence among under-five children. As such, this study sought to examine the sociodemographic factors that determine malaria among under-five children in Ghana. Methods. This paper used secondary data drawn from the 2008 Ghana Demographic and Health Survey. Bivariate analysis and complementary log-log regression models were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 10 publications
13
49
2
Order By: Relevance
“…The crude parasite rates are found to range from 10 to 70%, with Plasmodium falciparum accounting for 90-98%, Plasmodium malariae 2-9% and Plasmodium ovale 1% of all infections, respectively (Afudego, 2011). In their study, Nyarko and Cobblah (2014) found that the highest proportion (22.7%) of malaria under-five was reported among children whose mothers had primary school education, while mothers with higher education reported the lowest (17.4%) malaria cases among such children. The study further found the highest proportion of cases was reported among children whose mothers were from poor households, pointing to the fact that solving the malaria problem even among children might better be done through social and economic interventions rather than scientific-based interventions alone.…”
Section: Review Of Related Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…The crude parasite rates are found to range from 10 to 70%, with Plasmodium falciparum accounting for 90-98%, Plasmodium malariae 2-9% and Plasmodium ovale 1% of all infections, respectively (Afudego, 2011). In their study, Nyarko and Cobblah (2014) found that the highest proportion (22.7%) of malaria under-five was reported among children whose mothers had primary school education, while mothers with higher education reported the lowest (17.4%) malaria cases among such children. The study further found the highest proportion of cases was reported among children whose mothers were from poor households, pointing to the fact that solving the malaria problem even among children might better be done through social and economic interventions rather than scientific-based interventions alone.…”
Section: Review Of Related Literaturementioning
confidence: 93%
“…Empirical studies in Ghana (including Afudego, 2011;Nyarko & Cobblah, 2014) point to the fact that the group affected most by malaria are children under-five (accounting for 20% of the population) and pregnant women (accounting for 4% of the population). The crude parasite rates are found to range from 10 to 70%, with Plasmodium falciparum accounting for 90-98%, Plasmodium malariae 2-9% and Plasmodium ovale 1% of all infections, respectively (Afudego, 2011).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Plasmodium falciparum is the main species causing malaria infections in children around sub-Saharan Africa. It is estimated that 90% of the mortality is caused by Plasmodium falciparum (Anstey et al, 2002;Nyarko and Cobblah, 2014;Walldorf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Younger children (5-9 years) have higher risk of gametocyte carriage when infected with P. falciparum. A study in Tanzania has also reported similar association of age with increased gametocyte prevalence [36].…”
Section: Discussionmentioning
confidence: 63%